Characterisation of silicon nanoparticles produced by mechanical attrition using scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoemission spectroscopy - Unuigbe, David Moweme (Department of Physics, 2015)
Includes abstract.